The study of artificial lightings as a design factor in store window display - Sardea, Mayana M.; Florendo, Raquel Baltazar (1991.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Show windows -- Lighting; Lighting, Architectural and decorative